Synthesis of Selective β-Lactam Derivatives - Iyad Ali; Nina Sakhnini (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
In this work, the mild conditions of Mitsunobu reaction were used to convert the hydroxyl group of 6-triphenylmethylaminopenicillanyl alcohol to amines by using different nuleophiles such as phthalimide, di-tert-butyliminodicarboxylate and potassium cyanate. The existence of the β-lactam carbonyl group increased the instability towards nucleophilic attack of refluxing methanol and the four-membered ring was opened. Treating 3-Di-tert-Butoxycarbonylaminomethyl-6-triphenylmethylamino - penicillanate with 50% trifluoroacetic acid in dichloromethane, resulted in the cleavage of triphenylmethyl group and one tert-butyl group. While the removal of both triphenylmethyl groups as well as di-tert-butylamino carbonyl group occurred when 75% trifluoroacetic acid was used. The significance of this study is to synthesize β-lactam derivatives that might to be more resistant to degradation by β-lactamase and hence, therapeutically more effective.